Sampling with passive methods: an added value for the exposure assessment to fungal burden - Almeida, Beatriz (2019)
Projeto EXPOsE – Establishing protocols to assess occupational exposure to microbiota in clinical settings (02/SAICT/2016 – Project nº 23222).